Effects of turning over intensity on fatty acid metabolites in postharvest leaves of Tieguanyin oolong tea (Camellia sinensis) - Zixin Ni; Qingyang Wu; Ziwei Zhou; Yun Yang; Qingcai Hu; Huili Deng; Yucheng Zheng; Wanjun Bi; Zhenzhang Liu; Yun Sun (PeerJ, 2022)
Fatty acid derived volatiles (FADVs) are major contributors to the aroma quality of oolong tea (Camellia sinensis). Most of the processing time for oolong tea is taken up by turning over treatments, but the full profile of fatty acid metabolic changes during this process remains unclear. In this study, we detected fatty acids, their derived volatiles, and related genes of Tieguanyin oolong tea using biochemical and molecular biology methods. The results showed that with an increase in turning over intensities, the content of total unsaturated fatty acids continuously dropped and the content of characteristic FADVs, such as hexanoic acid (Z)-3-Hexenly ester and 2-exenal, continued to increase. Lipoxygenase (LOX), a key gene family in the fatty acid metabolic pathway, showed different patterns, and CsLOX1 (TEA025499.1) was considered to be a key gene during the turning over processes. We found that fruit-like aroma (Z)-3-Hexen-1-ol acetate had a strong correlation with the expression levels of eight Camelia sinensis LOX family genes. Tieguanyin had relatively rich pleasant volatile compounds with moderate turning over intensity (five times turning over treatments). This study provides an overall view of how fatty acid metabolites change and affect the quality of oolong tea with different turning over intensities during processing.